1989
DOI: 10.1161/01.str.20.6.809
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane synthesis inhibitor in a beagle pup model of perinatal asphyxia.

Abstract: During perinatal asphyxia, cerebral blood flow is markedly reduced in the gray and white matter of the telencephalon. Since previous work has implicated prostaglandins in the control of blood flow, we tested the hypothesis that a thromboxane synthesis inhibitor would improve cerebral blood flow and blunt the metabolic alterations that accompany asphyxia. Forty-three newborn beagles 2-7 days old were anesthetized, ventilated, and randomized to insult (5 minutes of asphyxia) or no insult and received treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…We speculate that 15-F 2t -IsoP may be a contributory factor in the hemodynamic compromise and periventricular brain injury in the premature neonate during oxidant stress; cyclooxygenase inhibitors, thromboxane synthase, and/or receptor blockers may attenuate the deleterious effects of oxidant stress. 47,48 …”
Section: Discussionmentioning
confidence: 99%
“…We speculate that 15-F 2t -IsoP may be a contributory factor in the hemodynamic compromise and periventricular brain injury in the premature neonate during oxidant stress; cyclooxygenase inhibitors, thromboxane synthase, and/or receptor blockers may attenuate the deleterious effects of oxidant stress. 47,48 …”
Section: Discussionmentioning
confidence: 99%
“…Studies in a beagle pup model of perinatal asphyxia have shown that treatment with the TXAS inhibitor CGS-13080 (pirmagrel), which increases PGI 2 activity and CBF in early phases of neonatal HIE, failed to show improvement in the ischemic metabolic changes. In addition, the pups had an increased risk of developing IVH (Ment et al, 1989). Although PGI 2 is among the prostanoids that could contribute to increased CBF in the early reperfusion phase of cerebral ischemia in newborns with HIE, a delayed increase in PGI 2 production or activity in later stages of HIE may have more beneficial effects.…”
Section: E Prostacyclin Metabolism and Hypoxic Ischemic Encephalopatmentioning
confidence: 99%
“…We speculate that the markedly greater PAF-induced brain microvascular constriction in the younger subjects may contribute to the hemodynamic compromise and periventricular brain injury observed in premature neonates exposed to oxidant stress. PAF antagonists, thromboxane synthase inhibitor, and/or receptor blockers may attenuate the deleterious effects of oxidant stress (4,25,28).…”
Section: Discussionmentioning
confidence: 99%